2007
DOI: 10.1001/archinte.167.5.476
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the War Back Home

Abstract: Background: Veterans of Operations Enduring Freedom and Iraqi Freedom (OEF/OIF) have endured high combat stress and are eligible for 2 years of free military service-related health care through the Department of Veterans Affairs (VA) health care system, yet little is known about the burden and clinical circumstances of mental health diagnoses among OEF/OIF veterans seen at VA facilities.Methods: US veterans separated from OEF/OIF military service and first seen at VA health care facilities between September 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
203
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 814 publications
(207 citation statements)
references
References 20 publications
4
203
0
Order By: Relevance
“…When entered into the same model simultaneously along with other factors, each remained a significant predictor, with mTBI history the most robust. PTSD and depression have been well documented in OIF/OEF veterans [6,23,[48][49][59][60][61][62][63][64][65][66][67]. This is a notable finding because other studies have found diminished effects of TBI when PTSD and depressive symptom severity were taken into account [6,62].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…When entered into the same model simultaneously along with other factors, each remained a significant predictor, with mTBI history the most robust. PTSD and depression have been well documented in OIF/OEF veterans [6,23,[48][49][59][60][61][62][63][64][65][66][67]. This is a notable finding because other studies have found diminished effects of TBI when PTSD and depressive symptom severity were taken into account [6,62].…”
Section: Discussionmentioning
confidence: 97%
“…As described elsewhere [46], International Classification of Diseases, 9th Revision, Clinical Modification [47] diagnostic codes in VHA administrative data for posttraumatic stress disorder (PTSD) and depression were used to identify these common disorders documented in OIF/OEF veterans [6,46,[48][49]. We limited this identification to codes assigned in two or more encounters [48] in primary care, mental health, women's health, or rehabilitation clinics or from an inpatient stay during fiscal years 2007-2009.…”
Section: Psychiatric Diagnosesmentioning
confidence: 99%
See 1 more Smart Citation
“…A sense of futility or hopelessness can further diminish the patient's willingness to participate in medical care. Detecting PTSD and trauma-related distress in the medical environment can be difficult to differentiate from traumatic brain injury (TBI) or symptoms due to other psychiatric disorders such as depression [26][27]. PTSD and depression have many symptoms in common, such as sleep disturbance, decreased participation in activities, estrangement from others, and decreased concentration.…”
Section: Posttraumatic Stress Disorder Patients In Medical Settingsmentioning
confidence: 99%
“…Many studies have aimed at estimating the prevalence of PTSD following deployment and have reported greatly varying rates. In general, higher PTSD prevalences have been found for the war in Iraq (9.8–19.9%) than for the war in Afghanistan (Hoge, Auchterlonie, & Milliken, 2006; Hoge et al, 2004; Seal, Bertenthal, Miner, Sen, & Marmar, 2007). These differences might, to some degree, reflect different methodological choices such as time of assessment, instruments and case definition, but they might also reflect actual differences in the toll of wars and missions (Sundin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%